Cellular Senescence in Diabetes Mellitus: Distinct Senotherapeutic Strategies for Adipose Tissue and Pancreatic β Cells - Takaaki Murakami; Nobuya Inagaki; Hiroshi Kondoh; Hiroshi Kondoh (Frontiers in Endocrinology, 2022)
Increased insulin resistance and impaired insulin secretion are significant characteristics manifested by patients with type 2 diabetes mellitus (T2DM). The degree and extent of these two features in T2DM vary among races and individuals. Insulin resistance is accelerated by obesity and is accompanied by accumulation of dysfunctional adipose tissues. In addition, dysfunction of pancreatic β-cells impairs insulin secretion. T2DM is significantly affected by aging, as the β-cell mass diminishes with age. Moreover, both obesity and hyperglycemia-related metabolic changes in developing diabetes are associated with accumulation of senescent cells in multiple organs, that is, organismal aging. Cellular senescence is defined as a state of irreversible cell cycle arrest with concomitant functional decline. It is caused by telomere shortening or senescence-inducing stress. Senescent cells secrete proinflammatory cytokines and chemokines, which is designated as the senescence-associated secretory phenotype (SASP), and this has a negative impact on adipose tissues and pancreatic β-cells. Recent advances in aging research have suggested that senolysis, the removal of senescent cells, can be a promising therapeutic approach to prevent or improve aging-related diseases, including diabetes. The attenuation of a SASP may be beneficial, although the pathophysiological involvement of cellular senescence in diabetes is not fully understood. In the clinical application of senotherapy, tissue-context-dependent senescent cells are increasingly being recognized as an issue to be solved. Recent studies have observed highly heterogenic and complex senescent cell populations that serve distinct roles among tissues, various stages of disease, and different ages. For example, in high-fat-diet induced diabetes with obesity, mouse adipose tissues display accumulation of p21Cip1-highly-expressing (p21high) cells in the early stage, followed by increases in both p21high and p16INK4a-highly-expressing (p16high) cells in the late stage. Interestingly, elimination of p21high cells in visceral adipose tissue can prevent or improve insulin resistance in mice with obesity, while p16high cell clearance is less effective in alleviating insulin resistance. Importantly, in immune-deficient mice transplanted with fat from obese patients, dasatinib plus quercetin, a senolytic cocktail that reduces the number of both p21high and p16high cells, improves both glucose tolerance and insulin resistance. On the other hand, in pancreatic β cells, p16high cells become increasingly predominant with age and development of diabetes. Consistently, elimination of p16high cells in mice improves both glucose tolerance and glucose-induced insulin secretion. Moreover, a senolytic compound, the anti-Bcl-2 inhibitor ABT263 reduces p16INK4a expression in islets and restores glucose tolerance in mice when combined with insulin receptor antagonist S961 treatment. In addition, efficacy of senotherapy in targeting mouse pancreatic β cells has been validated not only in T2DM, but also in type 1 diabetes mellitus. Indeed, in non-obese diabetic mice, treatment with anti-Bcl-2 inhibitors, such as ABT199, eliminates senescent pancreatic β cells, resulting in prevention of diabetes mellitus. These findings clearly indicate that features of diabetes are partly determined by which or where senescent cells reside in vivo, as adipose tissues and pancreatic β cells are responsible for insulin resistance and insulin secretion, respectively. In this review, we summarize recent advances in understanding cellular senescence in adipose tissues and pancreatic β cells in diabetes. We review the different potential molecular targets and distinctive senotherapeutic strategies in adipose tissues and pancreatic β cells. We propose the novel concept of a dual-target tailored approach in senotherapy against diabetes.